UPAYA MENINGKATKAN MINAT BELAJAR DAN PRESTASI BELAJAR SISWA PADA MATERI PEMBELAJARAN ALAT-ALAT OPTIK MELALUI PENDEKATAN SAINS TEKNOLOGI MASYARAKAT DI KELAS VIII SMPN 3 BELITANG MADANG RAYA - Wahid Gunarto; Nurul Hidayah (Universitas Sriwijaya, 2014)
This research was motivated by the state eighth grade students of SMP Negeri 3 Belitang Madang Raya in Â 20011/2012 academic year is a low learning interest and academic achievement are still many who have not reached the minimum completeness criteria (KKM). This research is classroom action research (CAR), which applying 3 cycles with details of pre-cycle , the first cycle and second cycle. The hypothesis of this study is action in the STM approach can improve learning and student achievement VIII.A grade SMP Negeri 3 Belitang Madang Raya on learning material optical instruments academic year 2011/2012 . The results of the data analysis showed that an increase in student interest of 1.37 % in the pre cycle and 0.8 % in first cycle. Student achievement has increased 1.9 % in pre-cycle and 4.45 in first cycle. Whereas in the classical classical completeness increased by 5 % in the pre cycle and 12.5 % in first cycle.